Feasibility analysis and techno-economic design of grid-isolated hybrid renewable energy system for electrification of agriculture and irrigation area: A case study in Dongola, Sudan. (15th September 2019) - Elkadeem, M.R.; Wang, Shaorong; Sharshir, Swellam W.; Atia, Eman G.
Highlights: A systematic framework for the optimal design of hybrid energy systems is proposed. The developed approach is applied to agriculture and irrigation area in Sudan. Effect of uncertainty parameters on system design and cost is examined. Solar-wind-diesel-battery-converter system is a cost-effective and reliable solution. Renewable resources and interest rate have high influences on investment decision. Abstract: Today, particular attention is being globally paid towards clean and sustainable energy system. The rapid development in renewable energy technologies, growth of energy markets, and adopted financial strategies and policies have the key role in achieving this target. This paper provides a comprehensive feasibility analysis of a gird-isolated hybrid renewable energy system for electrification of agriculture and irrigation area in Dongola, Sudan. A systematic and integrative framework combined with techno-economic optimization analysis for adequate planning and design of hybrid renewable energy system is proposed. Different hybridization cases of a solar photovoltaic, wind turbine, diesel generator, battery storage, and converter technologies, together with a diesel generator-based energy system as base case are modeled, evaluated and compared considering the stochastic behavior of renewable energy resources with a main target to find the most feasible and reliable solution with least system cost and realistic environmental impacts. This followed by a sensitivity analysis to reveal the effects of uncertainty in system parameters on the designed system and its economic performance. The obtained results indicate that solar-wind-diesel-battery-converter hybrid system is of optimal performance and superiority over the studied cases to serve the load demand of the investigated area. The system not only gets the minimum values of the total net present cost (24.16 M$) and levelized cost of energy (0.387 $/kWh), but also effectively achieves a positive return on investment of 39.94% and around 95% reduction in both carbon emissions and fuel consumption compared to the base case. Meanwhile, the result of sensitivity analysis demonstrates the high dependability of system cost on the volatility of solar radiation and wind speed as well as the changes in the rate of interest with the prospect of ignoring the effect of variation of diesel fuel price in the future investment decision. Finally, the output of this study is projected to raising the potentiality awareness of renewable energy in Sudan and providing a valuable reference about the optimal planning and utilization of hybrid renewable energy system in energy sector.